Effects of Coastal Construction on Indo-Pacific Humpback Dolphin (Sousa chinensis) Behavior and Habitat-Use Off Hong Kong - Piwetz, Sarah; Jefferson, Thomas A.; Würsig, Bernd (Frontiers in Marine Science, 2021)
Construction-related loss of habitat, degradation of existing habitat, noise pollution, and vessel activity are growing issues for Indo-Pacific humpback dolphins (Sousa chinensis) that occur in the shallow, near-shore, highly industrialized waters off Lantau Island, Hong Kong. We studied the occurrence of dolphins in discrete locations, fine-scale movement patterns, and dolphin behavioral activity states. Potential explanatory variables varied and included year, season, time of day, dolphin group size and behavioral activity state, proximity to construction activity, and vessel type and number. Land-based observations and theodolite tracking of dolphins and vessels were conducted from seven locations to the north of Lantau Island, Hong Kong, and marine construction activities near survey sites were identified. A total of 636 groups of dolphins were recorded, totaling 150.91 hours of tracking, from 405 days of observation effort. Hurdle models were used to analyze dolphin occurrence, multivariate generalized additive models (GAMs) were used to analyze fine-scale movement patterns, and log-likelihood ratio and binomial z score post hoc tests were used to analyze behavioral activity states. Dolphin occurrence was lower in historically important areas near long-term, low-intensity construction activity and dolphin swimming speed was higher in response to vessel presence. Overall, foraging and traveling were the most frequently observed behavioral activity states and resting behavior was observed off only one location that was not in proximity to construction activities. Temporal overlap in adjacent marine construction areas may displace animals for extended periods and nearby ecologically similar habitats should be identified and designated as marine protected areas to mitigate effects of such disturbance.